2014
DOI: 10.1073/pnas.1411098111
|View full text |Cite
|
Sign up to set email alerts
|

Solution structures of Mengovirus Leader protein, its phosphorylated derivatives, and in complex with nuclear transport regulatory protein, RanGTPase

Abstract: Cardiovirus Leader (L) proteins induce potent antihost inhibition of active cellular nucleocytoplasmic trafficking by triggering aberrant hyperphosphorylation of nuclear pore proteins (Nup). To achieve this, L binds protein RanGTPase (Ran), a key trafficking regulator, and diverts it into tertiary or quaternary complexes with required kinases. The activity of L is regulated by two phosphorylation events not required for Ran binding. Matched NMR studies on the unphosphorylated, singly, and doubly phosphorylated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
32
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 12 publications
(35 citation statements)
references
References 36 publications
2
32
0
Order By: Relevance
“…Interestingly, L E -2A interactions also clearly masked L E residue Y 41 , one of two crucial phosphorylation sites for the activity of L E . Phosphorylation is not required for L E interactions with Ran, but without these modifications, the subsequent complex cannot proceed to ternary or quaternary reactions required to trigger the Nup phosphorylation cascade (9). Therefore, logically, 2A cannot remain perpetually bound to L E during the normal course of events during infection.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Interestingly, L E -2A interactions also clearly masked L E residue Y 41 , one of two crucial phosphorylation sites for the activity of L E . Phosphorylation is not required for L E interactions with Ran, but without these modifications, the subsequent complex cannot proceed to ternary or quaternary reactions required to trigger the Nup phosphorylation cascade (9). Therefore, logically, 2A cannot remain perpetually bound to L E during the normal course of events during infection.…”
Section: Discussionmentioning
confidence: 99%
“…The control hGB1 alone did not allow this masking, either on the wild-type GST-L E or with the phosphomimetic bait, T 47 E. Therefore, Y 41 , which lies to the C-terminal side of the L E hinge domain, is among the likely contact sites for 2A binding. This site and T 47 were found to be solvent exposed when L E binds Ran (9).…”
Section: E -2a Interactionsmentioning
confidence: 95%
See 2 more Smart Citations
“…Eventually the active players (p38 and ERK-1/2) were identified for those Nup phosphorylation events, and for required modifications of the L protein itself (CK2 and Syk). Fitting the pieces together though, required NMR of the L:Ran complex (41) a superb technical feat by Valjean Bacot-Davis, a microbiology student who self-taught himself structural biology, just for this project. The structure(s) showed that L hijacks Ran, locking it into an irreversible GTP conformer.…”
Section: Nuclear Poresmentioning
confidence: 99%